The rose that grew from concrete - Shakur, Tupac, 1971-1996 (Pocket Books, 2009)
His talent was unbounded, a raw force that commanded attention and respect. His death was tragic -- a violent homage to the power of his voice. His legacy is indomitable -- remaining vibrant and alive. Here now, newly discovered, are Tupac's most honest and intimate thoughts conveyed through the pure art of poetry -- a mirror into his enigmatic life and its many contradictions. Written in his own hand at the age of nineteen, they embrace his spirit, his energy ... and his ultimate message of hope.